Large-scale wind power grid integration : technological and regulatory issues - Wang, Ningbo; Kang, Chongqing; Ren, Dongming (Academic Press, 2015)
Large Scale Wind Power Grid Integration: Technological and Regulatory Issues presents engineers with detailed solutions on the challenges of integrating and transmitting electricity generated from high power wind installations, covering all of the standard engineering issues associated with high power wind generation. The book includes detailed case studies from eight wind power bases in China, providing important insights for engineers in countries that are seeking to develop large-scale wind power farms. Also discussed is the emergence of 10 GW-level wind power bases that are now operational in China and those that are planned for offshore construction in Europe, the U.S., and other places in the world. China's leadership in Large-scale wind power bases with capacities over 1 GW (which already account for approximately 70%-80% of the total installed capacity in China) means that globally, engineers who are challenged with developing large-scale wind power installations can gain access to the experiences of Chinese engineers in this important technology.